A municipalização dos Objetivos do Milênio em Bairro Alto - GO: um olhar a partir da teoria da sociologia da ação organizada - Teixeira, Paulo Ricardo Loiola (2017)
This dissertation studies qualitatively the the factors that influence the process of localization of the Millennium Development Goals at Barro Alto, Goiás, Brazil, in order to understand the possibilities and limitations of this process. The analysis is relevant because of the many social and environmental challenges on the national and international level. Data have been collected in three phases: 1) analysis of the documentation and bibliography about the Millennium Development Goals and the Sustainable Development Goals; 2) Interviews with local actors and bibliographic studies; 3) Comparison between Barro Alto, Goiás, and Niquelândia, and the organization of the information according to the Sociology of the Organized Action. As a result, it was seen that Barro Alto, Goiás, can be considered a successful process of Millennium Development Goals implementation, with better numbers than the average of the Goiás state The analysis using the Organized Action Sociology framework facilitated the process of understanding the factors that influenced the success of the implementation of the MDG, such as social participation, transparency and the local capacity building.